1996
DOI: 10.1038/bjc.1996.40
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial and tumour localisation of the anti-EGFR monoclonal antibody ICR62 in head and neck or lung cancer

Abstract: Summary The purpose of this study was to determine the effect of the first rat monoclonal antibody (MAb ICR62) to the epidermal growth factor receptor (EGFR) in a phase I clinical trial in patients with unresectable squamous cell carcinomas. This antibody effectively blocks the binding of EGF, transforming growth factor (TGF)-oc and HB-EGF to the EGFR, inhibits the growth in vitro of tumour cell lines which overexpress the EGFR and eradicates such tumours when grown as xenografts in athymic mice. Eleven pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…In that trial, no serious toxicity was observed and four patients developed human anti-rat antibodies. Biopsies obtained from metastatic lesions showed localization of MAb ICR62 to the membranes of tumor cells, more prominently at higher doses (Modjtahedi et al, 1996). The fully human anti-EGF receptor mAb, ABX-EGF, has now entered phase I clinical trials (Yang et al, 2000).…”
Section: Anti-egfr Monoclonal Antibodies That Block Receptor Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…In that trial, no serious toxicity was observed and four patients developed human anti-rat antibodies. Biopsies obtained from metastatic lesions showed localization of MAb ICR62 to the membranes of tumor cells, more prominently at higher doses (Modjtahedi et al, 1996). The fully human anti-EGF receptor mAb, ABX-EGF, has now entered phase I clinical trials (Yang et al, 2000).…”
Section: Anti-egfr Monoclonal Antibodies That Block Receptor Kinasementioning
confidence: 99%
“…The need to ®nd an optimal biological dose for patients treated with these antibodies emphasizes the relevance of developing reliable biological markers in trials that evaluate agents acting on the EGFr. Although these early phase I trials with IMC-C225 did not include the analysis of biological markers, other trials with anti-EGFr antibodies and follow up studies with C225 and other anti-EGFr MAbs have shown that antibody binding to tumor EGFr and saturation of the receptors can be achieved (Modjtahedi et al, 1996;Perez-Soler et al, 1994. The pharmacokinetic ®ndings with C225 are in agreement with a prior phase I single dose clinical trial with a di erent murine anti-EGFr MAb, RG 83852, in patients with non-small cell lung cancer or head and neck tumors (Perez-Soler et al, 1994).…”
Section: Anti-egfr Monoclonal Antibodies That Block Receptor Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…non-small-cell lung cancer (NSCLC) is an aggressive solid tumour associated with a poor prognosis since surgery or chemotherapy is only beneficial in a fraction of all cases. Antibody-based therapy has been of limited success, but has been described using murine antibodies against targets such as the EGF-receptor in squamous cell carcinoma (Modjtahedi et al, 1996) or epithelial glycoprotein-2 for adenocarcinoma (Zimmermann et al, 1997). Such monoclonal antibodies probably may act by interfering in tumour cell signalling or through activation of complement and/or Fc receptor bearing cells.…”
mentioning
confidence: 99%
“…Over-expression of the epidermal growth factor receptor and p185 erbB-2 has been reported in a wide variety of human malignancies (Modjtahedi and Dean, 1994;Hynes and Stern, 1994) and has been found to correlate with poor prognosis in patients bearing these tumours. Importantly, these molecules have been used as targets for the therapy of human disease (Baselga et al, 1996;Modjtahedi et al, 1996). Relatively little is known about the expression of the recently discovered, related receptor, erbB-4 and its importance in human malignancy but a group of ligands, neuregulins, which bind to and activate this receptor have been described.…”
mentioning
confidence: 99%